Increase in Blood Brain Barrier Permeability, Oxidative Stress, and Activated Microglia in a Rat Model of Blast Induced Traumatic Brain Injury - Readnower, Ryan D. (2010)
Traumatic brain injury (TBI) as a consequence of exposure to blast is increasingly prevalent in military populations, with the underlying pathophysiological mechanisms mostly unknown. In the present study, we utilized an air-driven shock tube to investigate the effects of blast exposure (120 kPa) on rat brains. Immediately following exposure to blast neurological function was reduced. BBB permeability was measured using IgG antibody and evaluating its immunoreactivity in the brain. At 3 and 24 h post-exposure there was a transient significant increase in IgG staining in the cortex. At 3 days post-exposure IgG immunoreactivity returned to control levels. Quantitative immunostaining was employed to determine the temporal course of brain oxidative stress following exposure to blast. Levels of 4-hydroxynonenal (4HNE) and 3-nitrotyrosine (3NT) were significantly increased at 3 h post-exposure and returned to control levels at 24 h post-exposure. The response of microglia to blast exposure was determined by autoradiographic localization of (3)H-PK11195 binding. At 5 days post-exposure increased binding was observed in the contralateral and ipsilateral dentate gyrus. These regions also displayed increased binding at 10 days post-exposure; in addition to these regions there was increased binding in the contralateral ventral hippocampus and substantia nigra at this time point. Using antibodies against CD11b/c, microglia morphology characteristic of activated microglia was observed in the hippocampus and substantia nigra of animals exposed to blast. These results indicate that BBB breakdown, oxidative stress, and microglia activation likely play a role in the neuropathology associated with TBI as a result of blast exposure.